2020
DOI: 10.1186/s12885-019-6504-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review reporting quality of radiomics research in neuro-oncology: toward clinical utility and quality improvement using high-dimensional imaging features

Abstract: Background: To evaluate radiomics analysis in neuro-oncologic studies according to a radiomics quality score (RQS) system to find room for improvement in clinical use. Methods: Pubmed and Embase were searched up the terms radiomics or radiogenomics and gliomas or glioblastomas until February 2019. From 189 articles, 51 original research articles reporting the diagnostic, prognostic, or predictive utility were selected. The quality of the methodology was evaluated according to the RQS. The adherence rates for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 66 publications
7
64
4
1
Order By: Relevance
“…There were no studies that reported on cost-effectiveness, imaging used on phantom models, a prospectively validated radiomic signature in an appropriate clinical trial or performed clinical utility statistics (beyond just discussion of uses). 21 Further details are provided in Online Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no studies that reported on cost-effectiveness, imaging used on phantom models, a prospectively validated radiomic signature in an appropriate clinical trial or performed clinical utility statistics (beyond just discussion of uses). 21 Further details are provided in Online Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with other neuro-oncologic radiomic studies in the literature. 21 The RQS has some limitations, however. For example, greater emphasis is placed on the image-acquisition parameters 12 than on the image-normalization process (making the voxel, section thickness, and matrix size similar among MR imaging scans), despite the latter being important for optimal translation into multiinstitutional contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Radiomics Quality Score of our study was 13, which was 36% of the ideal score of 36. This was slightly higher than the average score of 11 assessed in the systemic review 34 .…”
Section: Methodsmentioning
confidence: 54%
“…(41-44) Radiomics features may be prone to biological validation for their correlation with disease pathology. (45) This observation is based on the hypothesis that radiomics features, especially second-order features, capture the spatial variation in signal intensity that may re ect the deposition of Aβ plaques. Further, it may extract different biological information from volume, (43,46) which is the traditional imaging biomarker of AD.…”
Section: Discussionmentioning
confidence: 99%